2020
DOI: 10.1128/aac.01814-20
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on Antimicrobial Agents: Remdesivir Treatment for COVID-19

Abstract: Remdesivir was recently approved by the Food and Drug Administration for the treatment of hospitalized patients with COVID-19. Remdesivir is the prodrug of an adenosine analogue that inhibits viral replication of several RNA virus families including Coronaviridae. Preclinical data in animal models of coronavirus diseases, including COVID-19, have demonstrated that early treatment with remdesivir leads to improved survival, decreased lung injury and decreased quantification of viral RNA. Recent clinical data ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 49 publications
1
59
0
Order By: Relevance
“…For example, while a recent meta-analyses reveal that patients treated with remdesivir receiving noninvasive oxygen support achieve higher recovery rates and lower mortality rates relative to patients on mechanical ventilation, 16 a preprint of an interim analysis of the World Health Organization (WHO) SOLIDARITY trial did not show a mortality benefit for remdesivir treatment among any patient group including those receiving respiratory support. 20 While the study's results must be interpreted in light of its methodological limitations, these findings have fueled ongoing debate on which COVID-19 patients would benefit from the use of remdesivir 21 and recently led the WHO to amend their own clinical guidelines to recommend against the use of remdesivir in hospitalized COVID-19 patients, due to perceived lack of consistent evidence of efficacy. 22 As with corticosteroids, uncertainty thus remains about the effectiveness of remdesivir across different patient populations, and the patient populations most appropriate for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while a recent meta-analyses reveal that patients treated with remdesivir receiving noninvasive oxygen support achieve higher recovery rates and lower mortality rates relative to patients on mechanical ventilation, 16 a preprint of an interim analysis of the World Health Organization (WHO) SOLIDARITY trial did not show a mortality benefit for remdesivir treatment among any patient group including those receiving respiratory support. 20 While the study's results must be interpreted in light of its methodological limitations, these findings have fueled ongoing debate on which COVID-19 patients would benefit from the use of remdesivir 21 and recently led the WHO to amend their own clinical guidelines to recommend against the use of remdesivir in hospitalized COVID-19 patients, due to perceived lack of consistent evidence of efficacy. 22 As with corticosteroids, uncertainty thus remains about the effectiveness of remdesivir across different patient populations, and the patient populations most appropriate for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that plitidepsin was 27.5-fold more potent than remdesivir, although it was also more cytotoxic (CC 50 = 1.99 to 200 nM versus 2 to 20 μM). Remarkably, remdesivir is the prodrug of an adenosine analogue which was approved by the Food and Drug Administration for treating hospitalized patients with COVID-19 ( 7 ). The rationale for testing plitidepsin against SARS-CoV-2 was that this compound was thought to target the host eEF1A protein ( 8 ).…”
Section: Textmentioning
confidence: 99%
“…As has long been appreciated for influenza virus treatment [ 1 , 2 •• ], early diagnosis and initiation of treatment significantly increases the chances of clinical benefit and reaching primary and secondary outcomes in COVID-19 therapeutic trials. In the double-blind, placebo-controlled ACTT-1 trial, patients who received remdesivir earlier had significantly greater clinical benefit which was greatest in patients who received the drug before six days after symptom onset [ 3 , 4 ]. The mortality benefit of anti-SARS-CoV-2 convalescent plasma has also been shown to be dependent on early initiation, albeit in a non-randomized fashion [ 5 ].…”
Section: Early Diagnosis and Treatment Are Paramount For Antiviral Therapeuticsmentioning
confidence: 99%